Evaluation of Pregnancy Outcome in Women with First Trimester Vaginal Bleeding: A Longitudinal Study at a Tertiary Care Hospital, Kolkata, India - Animesh Naskar; Rupsha Chowdhury; Pradip Kumar Saha; Rup Kamal Das (Journal of Clinical and Diagnostic Research, 2022)
Introduction: First trimester vaginal bleeding, a serious obstetric challenge to developing embryo, occurs in 15-25% of all pregnant women. It is a matter of great concern to both mother and obstetrician for its increased association of adverse maternal and foetal outcome. Aim: To measure the prevalence of patients with first trimester vaginal bleeding, to evaluate factors associated with it and to assess foeto-maternal outcome in those pregnant women. Materials and Methods: This was a hospital-based, longitudinal study carried out among 120 women with first trimester vaginal bleeding having normal body weight, and regular cycles and agreeing to follow-up, at Department of Obstetrics and Gynaecology in a tertiary teaching hospital, Kolkata, West Bengal, India, from January 2019 to June 2020. The incidence of vaginal bleeding in first trimester, its risk factors, foeto-maternal outcome in terms of Pregnancy Induced Hypertension (PIH), abortions, preterm deliveries, Antepartum Haemorrhages (APH), birth weight of baby, low Appearance or colour of the baby, Pulse, Grimace, Activity, and Respiration (APGAR) score at birth was assessed. The descriptive statistics was used to calculate percentage and mean and Chi-square-test with significance value considered at p-value <0.05. Results: Out of 4716 pregnant women attending in Obstetric clinic at their first trimester, 332 had vaginal bleeding, incidence being 7.04%. Out of 332 women, 120 study participants met inclusion criteria. Of 120 cases, 79 (65.8%) were from age group of 21-30 years. Highest incidence was 74 (61.7%) in primigravida. Incidence was high in poor socio-economic status (upper lower and lower) ie., 57 (47.5%) and unplanned cases, 87 (72.5%). On follow-up of 120 participants, 66 (55%) had threatened abortion, of them 51.5% (34/66) led to term pregnancy followed by preterm labour 39.4% (26/66) and only few, 9.09% (6/66) ended up with incomplete miscarriage. Spotting was most common nature of bleeding per vagina 41.7% (50/120). On follow-up of 60 (90.9%) viable pregnancies, PIH was in 12 (20%) cases and abruption was seen in one (1.6%). Majority of preterm babies 65.4% (17/26) needed Neonatal Intensive Care Unit (NICU) admission. Conclusion: Vaginal bleeding in first trimester is an indicator of the maternal and foetal adverse consequences and results of this study can enrich our knowledge to plan and manage these pregnant women adequately.